Perkawinan Nyuang Luh Ring Dura Desa Di Desa Pakraman Sembiran Kecamatan Tejakula Kabupaten Buleleng: Kajian Sosio-Religius - Gata, I Wayan; Subawa, Putu; Marselinawati, Putu Sri (Jayapangus Press, 2024)
Marriage in Hinduism is a phase of life that has the aim of raising offspring and creating a happy family based on God Almighty. Proposing to a woman is one part of the marriage procession, there is a unique thing about the procession of proposing to a woman in Sembiran Village which is called nyuang luh ring dura village, that is, if the prospective bride comes from outside Sembiran Village then she will be ceremonized like a new born baby. The prospective bride is given the Kepus Puser, Nelubulanin (3 monthly) and Ngotonin (7 monthly) ceremonies at the groom's place before holding the wedding ceremony. The aim of this research is to determine the socio-religious value of the nyuang luh ring dura marriage in Sembiran village. This research uses qualitative methods and uses qualitative descriptive analysis. Data collection methods in this research are interviews, documentation and literature study. The series of stages are reducing data, displaying data, validating data, and interpreting research data. The form of nyuang luh ring dura marriage (proposing marriage to a woman from outside) Sembiran Village has several stages, namely the initial stage, the core stage and the final stage. The socio-religious function in nyuang luh ring dura (proposing to a woman from outside) Sembiran Village is a social function, a function of family harmony, an aesthetic function. The socio-religious meaning of nyuang luh ring dura marriage (proposing to a woman from outside) Sembiran Village is the meaning of traditional survival, the meaning of tattwa, the religious meaning, and the meaning of spiritual awareness.